OPTIMALISASI BUDAYA LOKAL MELALUI PENDIDIKAN KARAKTER DAN PEMBERDAYAAN MASYARAKAT SEBAGAI STRATEGI PENINGKATAN KESEJAHTERAAN DI NAGARI SUNGAI JAMBUR, KEC. IX KOTO SEI LASI, KAB. SOLOK - Nofrion; Alyssa Humaira; Ibisanti Fatikasari; Rahmad Rifai Panjaitan; Nur'Aina Mardhatilla; Hanif Pandu Perdana (STKIP Subang, 2026)
Community Service (KKN) is a form of implementation of the Tri Dharma of HigherEducation in the field of community service, aimed at improving the quality of life ofthe community through various empowerment programs. The KKN program inSungai Jambur Village, IX Koto Sungai Lasi District, Solok Regency, focused onoptimizing local culture through character education and community empowermentas a strategy to improve community welfare. The work program included activitiesfor the Tataboga Hidayah MSME program, collaboration with the Carano MinangArt Studio, outreach on the impacts of drug use, outreach on stunting at integratedhealth posts (Posyandu), mentoring for dawn prayer activities, scouting training,and outreach on the dangers of gadgets.The Community Service (KKN) program in Sungai Jambur Village aims to optimizelocal cultural potential through character education and community empowermentas a strategy to improve welfare. The program implementation method uses aparticipatory approach, directly involving the community in each program.Implementation techniques include observation, interviews, outreach, training,mentoring, and activity evaluation. Results indicate increased public awareness ofthe importance of character education, health, local cultural preservation, andcommunity economic development through MSMEs. Furthermore, the youngergeneration is becoming more active in social, cultural, and religious activities.This Community Service Program (KKN) activity is expected to become asustainable community-based development strategy to improve the welfare of theSungai Jambur community.